Frequency of tongue anomalies among Yemeni children in dental clinics - Aljawfi, K. (University of Science and Technology, Yemen, 2014)
Objective: This study was designed to know the frequency of tongue anomalies and determine their relation with gender. Methods: This study was conducted on five hundreds Yemeni children, (250) boys and (250) girls with an age ranged from 6 -12 years. The sample was collected during the 2nd semester of 2013 from dental clinics, College of Dentistry, University of Sciences & Technology, Sana'a, Yemen. Children were examined with a disposable mouth mirrors, using gloves and gauze pads. Results: Fissured tongue (6.8%) was the most prevalent tongue anomalies, followed by geographic tongue (4.6%), then macroglossia (2.6%), after that ankyloglossia (2.2%), then hairy tongue (0.8%), and finally microglossia (0.4%). Conclusion: The frequency of tongue anomalies among Yemeni children was in boys more than girls. Fissured tongue was the commonest tongue anomaly, while the lowest one was microglossia.